The Effect of Lactation Education on the Success of Exclusive Breastfeeding in Postpartum Mothers - Yulianti, Nedisha Henny (International Journal of Nursing and Midwifery Research, 2024)
This study investigates the effect of providing lactation education on the success of exclusive breastfeeding in postpartum mothers. Exclusive breastfeeding is widely recognized for its numerous health benefits for both infants and mothers, yet many new mothers face challenges in maintaining exclusive breastfeeding. The objective of this research was to assess whether structured lactation education could improve breastfeeding outcomes during the postpartum period. A total of 200 postpartum mothers participated in the study, with 100 mothers receiving lactation education through group sessions and informational materials, while 100 mothers in the control group received standard postpartum care. The results indicated that the mothers who received lactation education were significantly more likely to practice exclusive breastfeeding at both 1 and 3 months postpartum compared to those who did not receive the education. The study found that lactation education helped to enhance maternal confidence, improve breastfeeding techniques, and address common challenges, leading to higher rates of exclusive breastfeeding. These findings support the importance of lactation education in promoting breastfeeding success and highlight the need for targeted educational interventions to improve maternal and infant health outcomes. However, the study also recognizes the influence of other factors, such as socio-economic status and social support, on breastfeeding success, suggesting that a comprehensive approach that includes education, support, and community engagement is essential for achieving optimal breastfeeding practices.